A global view of cross-border migration - Julia Di Giovanni; Andrei A. Levchenko; Francesc Ortega (Institute for the Study of Labor (IZA), 2012)
This paper evaluates the welfare impact of observed levels of migration and remittances in both origins and destinations, using a quantitative multi-sector model of the global economy calibrated to aggregate and firm-level data on 60 developed and developing countries. Our framework accounts jointly for origin and destination characteristics, as well as the inherently multi-country nature of both migration and other forms of integration, such as international trade and remittance flows. In the presence of firm heterogeneity and imperfect competition larger countries enjoy a greater number of varieties and thus higher welfare, all else equal. Because of this effect, natives in countries that received a lot of migration - such as Canada or Australia - are better off. The remaining natives in countries with large emigration flows - such as Jamaica or El Salvador - are also better off due to migration, but for a different reason: remittances. The quantitative results show that the welfare impact of observed levels of migration is substantial, at about 5 to 10% for the main receiving countries and about 10% for the main sending countries.
urn:nbn:de:101:1-201303182279
Keywords: F12; F15; F22; F24; 330; migration; remittances; international trade; welfare; Internationale Wanderung; Rücküberweisung (Migranten); Außenwirtschaft; Wohlfahrtsanalyse; Welt